Effects of sediment on mechanical behavior of polypropylene fiber concrete before and after exposure to high temperature - Bilel Boulakoud (The Journal of Engineering and Exact Sciences)
The phenomenon of siltation of dams causes in Algeria a vital problem which annually loses a considerable volume of water storage.The objective of this study the valorization of calcined sediment from the Fergoug dam (western Algeria) in normal concrete exposed at 800 °C. Moreover, the sediments were calcination-treated at 750°C for 5 hours tomakeitactive. The different mixtures were prepared with 0%, 8%, 12% and 16% of  sediment by partial substitution of  cement , as well as of polypropylene fiber volume of 0.05% and 0.1%. All mixes  were investigated on compressive strength and flexural strength at 90 days with different heating cooling cycles from the room temperature to 800 °C in electric muffle furnace. The experimental result indicates that the inclusion 8 and 12% of calcined sediment with fiber significantly enhances properties of normal concrete before and after heating, respectively.